Delineation of aquifer storage potential in response to regional groundwater development - Joseph Omeiza Alao; Hammed A. Lawal; Momohjimoh Abdulsalami; Fahad Abubakar; Obanero O. Abduwahab; Ekwu Tongha Mary; Mumeen Adebayo Yusuf (Discover Water, 2024)
Abstract Developing aquifers as part of sustainability efforts toward groundwater development is a tactical approach to meeting water demand and management objectives. Delineation of aquifer storage potential (ASP) and longitudinal conductance ( $${S}_{L}$$ S L ) is a good approach to protect and manage groundwater resources. A Schlumberger configuration was applied to delineate fifteen (15) vertical electrical sounding (VES) stations alongside a 2D electrical resistivity imagery (ERI) profile and regional borehole data to characterize the regional ASP. The results of the study show that the layer resistivity and thickness values of the regional aquifer unit range from 39.9–105 Ωm and 15–44 m, respectively, while the overburden thickness overlays the regional aquifer unit varied between 5–10 m corresponding to the regional borehole data. The weathered/fractured basemen, which constitute the regional aquifer unit were delineated, which consists of shallow, moderate, and deep aquifer zones. The deep aquifer zones fall within the depth of 30–44 m and are considered suitable for groundwater prospective. The weathered layer with appreciably low resistivity values with thick aquifer regolith has also been identified as most suitable for borehole siting. The weathered/fractured encountered within thick aquifer regolith were mapped as the region with a high ASP for groundwater development. In addition, the values of longitudinal conductance, $${S}_{L}$$ S L and transverse resistance, $${R}_{T}$$ R T estimated from aquifer parameters vary between $$0.21-0.85 \,{Ω }^{-1}$$ 0.21 - 0.85 Ω - 1 and $$1695-3124\, {Ω m}^{2}$$ 1695 - 3124 Ω m 2 , respectively. The $${S}_{L}$$ S L values show that the study area falls within moderate ( $$0.20-0.69 \,{Ω }^{-1}$$ 0.20 - 0.69 Ω - 1 ) and good ( $$0.7-4.9 \,{Ω }^{-1}$$ 0.7 - 4.9 Ω - 1 ), which invariably determined the regional aquifer protective capacity. Thus, the DC geoelectrical approach has been successfully employed in a lateritic-based environment to delineate aquifer-promising zones for regional groundwater development.